H-NS family protein MvaU downregulates phenazine-1-carboxylic acid (PCA) biosynthesis via binding to an AT-rich region within the promoter of the phz2 gene cluster in the rhizobacterium Pseudomonas strain PA1201 - Yun-Ling Fang; Ying Cui; Lian Zhou; Chitti Thawai; Tatheer Alam Naqvi; Hongyan Zhang; Ya‐Wen He (Synthetic and Systems Biotechnology, 2021)
expression. These findings detail a new MvaU-dependent regulatory pathway of PCA biosynthesis in PA1201 and provide a foundation to increase PCA fermentation titer by genetic engineering.
Keywords: Bacterial Genetics and Biotechnology; Bacterial biofilms and quorum sensing; Bacteriophages and microbial interactions